2022
DOI: 10.2147/jir.s372751
|View full text |Cite
|
Sign up to set email alerts
|

C-X-C-Chemokine-Receptor-Type-4 Inhibitor AMD3100 Attenuates Pulmonary Inflammation and Fibrosis in Silicotic Mice

Abstract: Background Silicosis is a severe pulmonary disease caused by inhaling dust containing crystalline silica. The progression of silicosis to pulmonary fibrosis is usually unavoidable. Recent studies have revealed positivity for the overexpression of C-X-C chemokine receptor type 4 (CXCR4) in pulmonary fibrosis and shown that the CXCR4 inhibitor AMD3100 attenuated pulmonary fibrosis after bleomycin challenge and paraquat exposure. However, it is unclear whether AMD3100 reduces crystalline silica-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…After treatment with AMD3100, the increase in neutrophils caused by CS exposure was reversed, the number of lymphatic aggregates around blood vessels decreased, and pulmonary fibrosis improved. At the same time, blocking the CXCR4/CXCL12 axis also effectively reduced the number of B cells in peripheral blood and inhibited the migration of B cells to the lungs 117 …”
Section: Cxcr4/cxcl12 Axis–mediated Inflammatory Diseasesmentioning
confidence: 95%
See 4 more Smart Citations
“…After treatment with AMD3100, the increase in neutrophils caused by CS exposure was reversed, the number of lymphatic aggregates around blood vessels decreased, and pulmonary fibrosis improved. At the same time, blocking the CXCR4/CXCL12 axis also effectively reduced the number of B cells in peripheral blood and inhibited the migration of B cells to the lungs 117 …”
Section: Cxcr4/cxcl12 Axis–mediated Inflammatory Diseasesmentioning
confidence: 95%
“…116 CXCR4 also plays a vital role in pulmonary fibrosis. Sun et al 117 reported that the infiltration of neutrophils, lymphocytes, and B cells in the lungs increased and the expression of the CXCR4/CXCL12 axis was upregulated in mice with crystalline silica (CS)-induced pulmonary fibrosis, resulting in alveolar damage and abnormal thickening of the bronchial wall. After treatment with AMD3100, the increase in neutrophils caused by CS exposure was reversed, the number of lymphatic aggregates around blood vessels decreased, and pulmonary fibrosis improved.…”
Section: Cxcl12/cxcr4 Axis In Pulmonary Inflammationmentioning
confidence: 99%
See 3 more Smart Citations